Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3802/jgo.2011.22.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Visual inspection with acetic acid for detection of high grade lesion in atypical squamous cells and low grade squamous intraepithelial lesions from cervical Pap smear

Abstract: ObjectiveTo evaluate the value of visual inspection with acetic acid (VIA) test to detect high grade lesion in women with atypical squamous cells or low grade squamous intraepithelial lesions cervical cytology.MethodsWomen with atypical squamous cells or low grade squamous intraepithelial lesions who were scheduled to undergo colposcopy at Vajira Hospital and met inclusion criteria were included. All participants underwent VIA test prior to usual steps of colposcopy. The VIA results were interpreted as positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Earlier studies have evaluated pap smear cytology, VIA with magnification (VIAM), visual inspection with Lugol's iodine (VILI) and HPV detection as the “triaging” tests for VIA. Studies evaluating Pap smear cytology or VIAM to triage VIA positive women did not observe significant benefits . Studies conducted in Zimbabwe and in India observed significant improvement in predictive value without any loss of sensitivity when HPV test was used to triage the VIA positive women .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Earlier studies have evaluated pap smear cytology, VIA with magnification (VIAM), visual inspection with Lugol's iodine (VILI) and HPV detection as the “triaging” tests for VIA. Studies evaluating Pap smear cytology or VIAM to triage VIA positive women did not observe significant benefits . Studies conducted in Zimbabwe and in India observed significant improvement in predictive value without any loss of sensitivity when HPV test was used to triage the VIA positive women .…”
Section: Discussionmentioning
confidence: 95%
“…Studies evaluating Pap smear cytology or VIAM to triage VIA positive women did not observe significant benefits. 29,30 Studies conducted in Zimbabwe and in India observed significant improvement in predictive value without any loss of sensitivity when HPV test was used to triage the VIA positive women. 31.32 However, both the studies were hospital based and among small number of subjects.…”
Section: Accuracy Of Via and Hc II Tests Used Sequentiallymentioning
confidence: 99%
“…23,24 Pothisuwan M et al emphasized the significance of VIA that it may reduce the necessity of colposcopy which was in concordance with our study. 25 Ghosh P found, all biopsy positive cases (CIN I or worse) were VILI positive. 3 In Colposcopy, sensitivity was 83%, specificity 86%, PPV 51.3%, NPV 96.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the incidence of cervical intraepithelial neoplasia (CIN) 2-3/adenocarcinoma in situ (AIS) ranged from 8.0% to 18.5% (Kiatpongsan et al, 2006;Kantathavorn et al, 2008;Suntornlimsiri, 2010;Poomtavorn et al, 2011;Pothisuwan et al, 2011;Ekalaksananan et al, 2011;Kingnate et al, 2014;). These findings were in line with previous studies from North America (Levi et al, 2003;Boardman et al, 2006;Selvaggi, 2006;Sherman et al, 2006;Srodon et al, 2006;Feng and Husain, 2007;Safaeian et al, 2007Siddiqui et al, 2008.…”
Section: Atypical Squamous Cells Of Undetermined Significancementioning
confidence: 99%
“…In a region with a low incidence of cervical cancer, positive smear results for LSIL were associated with CIN2-3/AIS in approximately 12%-18% of women on initial colposcopy and with less than 1% of underlying invasive cancer (Massad et al, 2001;ALTS Group, 2003;Fairman et al, 2004;Chute et al, 2006). In Thailand, reported incidence of significant cervical pathology ranges from 11.2% to 32.2% (Table 2) (Khuakoonratt et al, 2008;Boonlikit, 2008;Kiatiyosnusorn et al, 2010;Ekalaksananan et al, 2011;Pothisuwan et al, 2011;Kingnate et al, 2014). The significant finding noted in some studies in Thailand is a relatively high incidence of underlying high-grade cervical lesion (11.2%-30.3%) and invasive lesion (1.3%-1.9%) (Khuakoonratt et al, 2008;Kiatiyosnusorn et al, 2010).…”
Section: Low-grade Squamous Intraepithelial Lesionmentioning
confidence: 99%